Exploring Potential Links Between Co-occurring Coastal Terrestrial and Marine Heatwaves in Australia - Pathmeswaran, Charuni; Sen Gupta, Alex; Perkins-Kirkpatrick, Sarah E.; Hart, Melissa Anne (Frontiers in Climate, 2022)
Despite numerous studies examining terrestrial or marine heatwaves independently, little work has investigated potential associations between these two types of extreme events. Examination of a limited number of past events suggests that certain co-occurring terrestrial and marine heatwaves have common drivers. Co-occurring events may also interact via local land-sea interactions, thereby altering the likelihood of these events. This study explores possible links between adjacent coastal marine and terrestrial heatwaves around Australia using observation and reanalysis data. We find a significant increase in the number of terrestrial heatwave days in the presence of an adjacent co-occurring marine heatwave along the coastal belt of Australia. In most regions, this increase persists at least 150km inland. This suggests that processes operating beyond the narrow coastal belt are important in most regions. We also show that synoptic conditions driving a terrestrial heatwave in three locations around Australia are conducive for warming the ocean, which would increase the likelihood of a marine heatwave occurring. Our findings suggest that co-occurring terrestrial and marine heatwaves co-occur more frequently than chance would dictate, and that large scale synoptics may be conducive to both coastal terrestrial and marine heatwaves.